Effect of milk proteins aggregation using Transglutaminase and Maillard reaction on Ca2+ milk gel - Alfayadh, Hassan Mahdi; Hamk, Mohammed Latif; Ibrahim, Kocher Jamal; Al-Saadi, Jasim Mohammed (Kurdistan Journal of Applied Research, 2018)
Effect of transglutaminase, Maillard reaction induced crosslinking and the combination of transglutaminase and Maillard reaction induced crosslinking between whey proteins and caseins in milk on calcium milk gel properties were investigated. Treatment of milk with transglutaminase, Maillard reaction, and transglutaminase + Maillard reaction cause to the appearance of new high MW protein bands. Water holding capacity, gel strength and sensory scores of gel samples increased and spontaneous whey separation decreased in calcium-induced milk gel made from transglutaminase and combination of transglutaminase and Maillard reaction treated milk compare with calcium-induced milk gel made from untreated milk alone.